Preventing unnecessary referrals into specialist mental health services: an interrupted time-series evaluation of a new primary care-linked mental health service. Issue 4 (2nd September 2021) - Healey, Andrew; Melaugh, Alexandra; Demetriou, Len; Power, Tracey; Sevdalis, Nick; Pritchard, Megan; Goulding, Lucy
Abstract : Purpose: Many patients referred by their GP for an assessment by secondary mental health services are unlikely to ever meet eligibility thresholds for specialist treatment and support. A new service was developed to support people in primary care. "the authors evaluate" whether the phased introduction of the Lambeth Living Well Network (LWN) Hub to a population in south London led to: a reduction in the overall volume of patients referred from primary care for a secondary mental health care assessment; and an increase in the proportion of patients referred who met specialist service eligibility criteria, as indicated by the likelihood of being accepted in secondary care. Design/methodology/approach: The evaluation applied a quasi-experimental interrupted time series design using electronic patient records data for a National Health Service (NHS) provider of secondary mental health services in south London. Findings: Scale-up of the Hub to the whole of the population of Lambeth led to an average of 98 fewer secondary care assessments per month (95% CI −118 to −78) compared to an average of 203 assessments per month estimated in the absence of the Hub; and an absolute incremental increase in the probability of acceptance for specialist intervention of 0.20 (95% CI; 0.14 to 0.27) above an average probability of acceptance of 0.57 in the absence of the Hub. Research limitations/implications: Mental health outcomes for people using the service and system wide-service impacts were not evaluated preventing a more holistic evaluation of the effectiveness and cost-effectiveness of the LWN Hub. Practical implications: Providing general practitioners with access to service infrastructure designed to help people whose needs cannot be managed within specialist mental health services can prevent unnecessary referrals into secondary care assessment teams. Social implications: Reducing unnecessary referrals through provision of a primary-care linked mental health service will reduce delay in access to professional support that can address specific mental-health related needs that could not be offered within the secondary care services and could prevent the escalation of problems. Originality/value: The authors use NHS data to facilitate the novel application of a quasi-experimental methodology to deliver new evidence on whether an innovative primary care linked mental health service was effective in delivering on one of its key aims.